Il De modo audiendi confessiones di Heinrich Lur e la penitenza sacramentale nel basso medioevo - Colombo, Lorenzo (FrancoAngeli, 2022)
Since the central centuries of the Middle Ages the sacrament of penance became one of the central aspects of religious life and Christian practice. To help the clergy tasked with pastoral care in listening penitents' confessions manuals were penned, which are to this day not much studied. The analysis of one of these texts, the De modo audiendi confessiones of Heinrich Lur, canon in the cathedral of Trento around the half of the fifteenth century, is the occasion to reflect on what in the late Middle Ages revolved around the administration of sacramental penance, in regards to theology and canon law as well as pastoral care.